Asthmatic bronchial epithelial cells have a deficient innate immune response to infection with rhinovirus - Wark, Peter A.B.; Johnston, Sebastian L.; Bucchieri, Fabio; Powell, Robert; Puddicombe, Sarah; Laza-Stanca, Vasile; Holgate, Stephen T.; Davies, Donna E. (The Journal of experimental medicine, 2005)
Rhinoviruses are the major trigger of acute asthma exacerbations and asthmatic subjects are more susceptible to these infections. To investigate the underlying mechanisms of this increased susceptibility, we examined virus replication and innate responses to rhinovirus (RV)-16 infection of primary bronchial epithelial cells from asthmatic and healthy control subjects. Viral RNA expression and late virus release into supernatant was increased 50- and 7-fold, respectively in asthmatic cells compared with healthy controls. Virus infection induced late cell lysis in asthmatic cells but not in normal cells. Examination of the early cellular response to infection revealed impairment of virus induced caspase 3/7 activity and of apoptotic responses in the asthmatic cultures. Inhibition of apoptosis in normal cultures resulted in enhanced viral yield, comparable to that seen in infected asthmatic cultures. Examination of early innate immune responses revealed profound impairment of virus-induced interferon-β mRNA expression in asthmatic cultures and they produced >2.5 times less interferon-β protein. In infected asthmatic cells, exogenous interferon-β induced apoptosis and reduced virus replication, demonstrating a causal link between deficient interferon-β, impaired apoptosis and increased virus replication. These data suggest a novel use for type I interferons in the treatment or prevention of virus-induced asthma exacerbations.